"Still Life with Vitamins: Art and Science at the 1939 New York World's Fair". (27th January 2016) - Lutz, Raechel
Abstract: At the 1939 New York World's Fair, artist Witold Gordon created a mural depicting common foods such as dairy, fruits, vegetables, and seafood on the exterior of the main food exhibition hall. Alongside the foods of the mural, Gordon painted vitamins in little circles and letters. This essay argues that the inclusion of vitamins in the mural illustrates a moment when nutritional science was becoming an important way of understanding the relationship between food and health. To do this conceptual work, Gordon played with abstraction and painterly styles to create a scene that both emulated the scientific message of the fair and depicted reverence toward nature as a guiding force in human life. The end result was an optimistic still-life mural that demonstrated the effort to popularize scientific ideas about vitamins and nutrition to the American public in the 1930s.